Oral squamous cell carcinoma: a clinicopathological study on 194 cases in northeastern Brazil. A cross-sectional retrospective study - Leite, Amanda Almeida (2018)
BACKGROUND: Only a few studies have evaluated the clinicopathological features of oral squamous cell carcinoma (SCC) in Brazil, and most were conducted in the most industrialized region of the country, i.e. the southeastern region. The aim of this study was to evaluate the clinicopathological features of this malignant neoplasm in northeastern Brazil. DESIGN AND SETTING: Retrospective study performed in an oral pathology laboratory in Recife, Brazil. METHODS: All cases of oral SCC that occurred between 2000 and 2015 were studied. Clinical data were recorded and histological slides were reviewed. Statistical analysis was performed using the chi-square test (P ≤ 0.05). RESULTS: A total of 194 cases were evaluated. The male-to-female ratio was 1.5:1. The mean age was 65.4 years, and only 6.6% of the cases occurred in patients younger than 41 years. Most tumors consisted of well-differentiated SCC (54.6%). CONCLUSIONS: The findings of this study highlight the higher prevalence of oral SCC among women and the increasing number of cases among young patients. Thus there is no specific risk group for oral SCC, as in the past. This fact needs to be taken into consideration in clinical routine care, so that apparently innocuous malignant lesions do not go unnoticed in these individuals.